The Construction of the Meaning of the Boycott According to the Boycotters on the Israeli-Palestinian Issue - Yolanda Tristania Ashari; Lusy Mukhlisiana (Publikasi Indonesia, 2024)
The boycott movement is a public action in response to the genocide situation between Israel and Palestine, which was highlighted by the media at the end of 2023. The public uses all forms of media to spread awareness as widely as possible regarding this boycott movement, one of which is using social media. However, this action did not last long, as can be seen from the fact that several outlets considered pro-Israel were busy again after several months of the boycott movement. So this research was conducted with the aim of finding out the construction of the meaning of boycott according to people who boycott products with the Pro-Israel label. This research focuses on how people construct meaning in a movement that is currently being carried out by society, namely the boycott movement as part of cancel culture. This research was conducted using qualitative research methods with a phenomenological approach proposed by Alfred Schutz to find out how the intrapersonal communication of each boycott perpetrator was formed into a personal construction of meaning regarding the boycott movement they carried out.